HISTORY OF CHRONICLES AS AN EDITORIAL WORKS: Editorial analysis of the Book of Chronicles, Ezra and Nehemiah - Pieter Anggiat Napitupulu; Agus Santoso; Bobby Kurnia Putrawan (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2021)
The books of Chronicles (1 and 2 Chronicle), Ezra and Nehemiah usually been understood as three separate books, written by different authors. But lately The Old Testament experts claim, that these three books were written in a school called Historical Work of Chronicles or